EFEKTIFITAS PENGGUNAAN METODE PEMBELAJARAN TEAM PRODUCT UNTUK MENINGKATKAN KEMAMPAUAN BERPIKIR LOGIS ANAK USIA DINI - Pertiwi, Hana; Masitoh, Siti; Andrisyah, Andrisyah (IKIP Siliwangi, 2020)
Early childhood is a child in thegrowt age range zero up to eight years old.. At this age the child's cognitive ability began to develop optimally. Among the cognitive ability is the ability to thinking logically. The ability of logical thinking ability is thinking which corresponds to the power of reason in general, or a reasonable thinking sometimes people call it.Cognitive ability of logical thinking ability especially child basically can continue to rise by itself in line with its growth. Nevertheless, the role of adults primarily parents and teachers also can help early childhood in enhancing of logical thinking. One of the learning methods which recomended for teacher set about developing logical thinking ability is aTeam Product Learning Method.The methode of research ispseudo-experimentation or quasi experiments methods. While the research design is used is